Analysis of the Risk Factors for Mortality in Adult COVID-19 Patients in Wuhan: A Multicenter Study - Li, Man; Cheng, Biao; Zeng, Wen; Chen, Sichao; Tu, Mengqi; Wu, Meng; Tong, Wei; Wang, Shipei; Huang, Yihui; Long, Wei; Zhou, Wei; Chen, Danyang; et al. (Frontiers in Medicine, 2020)
Abstract Objectives: An outbreak of coronavirus disease (COVID-19) in 2019 in Wuhan, China, has spread quickly worldwide. However, the risk factors associated with COVID-19-related mortality remain controversial. Methods: 245 adult patients with laboratory-confirmed COVID-19 from two centers were analyzed. Chi-square test, Fisher’s exact test and the Mann-Whitney U test were used to compare the clinical characteristics between the survivors and non-survivors. To explore the risk factors associated with in-hospital death, univariable and multivariable cox regression analyses were used. Results: Of the 245 patients included in this study, 23 (9.4%) died in the hospital. The multivariate regression analysis showed increased odds of in-hospital deaths associated with age, D-dimer levels >1000 ng/L, platelet count < 125, and higher serum creatinine levels. Conclusions: We identified risk factors that show significant association with mortality in adult COVID-19 patients, and our findings provide valuable references for clinicians to identify high-risk patients with COVID-19 at an early stage.